Economic Activities of German Local Authorities – Critical Notes from a Public Finance Perspective - Thomas Döring; Birgit Aigner-Walder (Central European Public Administration Review)
Within the last two decades, local authorities throughout Germany have increased their revenue by stepping up their economic activities. Municipal business ventures range from energy supply to catering services and even food retail, and are almost all justified by some public purpose or other. In 2010, local authorities in western Germany earned 5.3 pc of total revenue from their economic activities, compared to 4.7 pc in 1992. The share in eastern Germany was rising over the same period from 4.3 pc to 5.1 pc. In fact in 2010 a total of € 9.3 billion was earned by local authorities this way (compared to € 6.0 billion in 1992). The aim of the paper is to examine this trend from the perspective of public finance by drawing on the theory of public goods, the theory of fiscal federalism and some aspects of new political economy. Although the results vary somewhat depending on the angle taken, on balance the new economic activities by local government in Germany must be assessed negatively.